Junior Hockey Employment Lawsuit on Thin Ice; Judges Refuse to Ok $30-Million Deal - Perkel, Colin (CBC, 2020)
A $30-million settlement of three class actions over the alleged failure to pay junior hockey players the minimum wage has been thrown into jeopardy after three judges refused to sign off on the agreement.

Canadian Hockey League Settles Lawsuits Filed by Current, Former Players Over Back Pay - Canadian Press (CBC, 2020)
The Canadian Hockey League on May 15 settled three class-action lawsuits filed by current and former junior players seeking back pay for minimum wage.

Deindustrialization – and the Politics of Our Time (2020)
Examines the political responses to deindustrialization as well as its historical roots and lived experiences.DéPOT is a partnership of over 35 research centres, industrial museums, labour archives, trade unions and other organizations across Italy, France, Germany, the UK, Canada and the United States. [Funded by the Humanities and Social Sciences Research Council.]

The CHL Players’ Class Action – Players’ Victory or CHL Shutout? - Thornicroft, Kenneth Wm. (CanLII Connects, 2020)
Are “major junior” hockey players amateur athletes honing their skills with a view to playing professional hockey, or employees working in for-profit businesses? This question lies at the heart of the ongoing class actions involving the Canadian Hockey League (“CHL”) and its member leagues and teams (the “CHL Litigation”). –From introduction